E3 ligase Trim35 inhibits LSD1 demethylase activity through K63-linked ubiquitination and enhances anti-tumor immunity in NSCLC - Feiyu Tang; Can Lu; Xiang He; Wei Lin; Bowen Xie; Xing Gao; Yang Peng; Desong Yang; Lunquan Sun; Liang Weng (Cell Reports, 2023)
Summary: Targeting lysine-specific histone demethylase 1A (LSD1) can improve tumor immunogenicity of poorly immunogenic tumors, such as non-small cell lung cancer (NSCLC), with elevated T cell infiltration and sensitize tumors to anti-PD-1 therapy. However, the lack of reliable biomarkers limits utilization of LSD1 inhibitors in cancer therapy. Here, we identify an E3 ligase, Trim35, as an effective biomarker for high activity of LSD1 to predict prognosis of LSD1-targeted therapy as well as immunotherapy. Mechanistically, Trim35 represses LSD1 demethylase activity by mediating K63 ubiquitination at lysine site 422 of LSD1. Suppressed LSD1 activity facilitates ERGIC1 transcription, followed by autophagy inhibition and IFNGR1 stabilization to activate IFN-γ signaling, leading to increased MHC class I expression and immune surveillance of NSCLC cells. Furthermore, combinational use of an LSD1 inhibitor and anti-PD-1 therapy can significantly eradicate poorly immunogenic lung cancer with low Trim35. These findings strongly suggest that Trim35 is a promising biomarker for prediction of immunotherapy outcome in NSCLC.